Corneal Endothelial Morphological Alterations in Type 2 Diabetes: Associations with Glycemic Control, Disease Duration, and Diabetic Retinopathy Severity—A Cross-Sectional Study in Benghazi, Libya - Geilani, Nadia Abdelsalam; Julio, Gemma; Abdala, Majdi Abdulhamid (Libyan international medical university journal, 2023)
Background The corneal endothelium is essential for maintaining corneal transparency and fluid regulation, and its dysfunction can lead to corneal edema and decreased visual acuity. Corneal specular microscopy is used to detect corneal disorders early. Aim This study aimed to evaluate morphological changes in the corneal endothelium of patients with type 2 diabetes mellitus (DM) using specular microscopy. Methods This study enrolled 50 individuals with type 2 diabetes and 50 nondiabetic individuals as control subjects. Patients with certain ocular and systemic conditions were excluded. The collected data included demographic information, medical history, recent hemoglobin A1c (HbA1c) values, visual acuity, ophthalmological examination, and diabetic retinopathy (DR) staging. The corneal endothelial morphology was evaluated using a noncontact specular microscope, which measured corneal endothelial cell density (ECD), central corneal thickness (CCT), coefficient of variation of cell size (CV), and hexagonality. The data were analyzed using SPSS software, and the results were presented as mean ± standard deviation, numbers, and percentages. An unpaired t-test was used to compare different means, and a p-value less than 0.05 was considered statistically significant. Results A majority of diabetic patients (62%) had diabetes for more than 10 years, and 58% of them had higher than 7.5% HbA1c levels. In terms of DR severity, 46% of patients had mild nonproliferative diabetic retinopathy (NPDR), 36% had moderate NPDR, and 10% had severe NPDR. There were significant differences between diabetic and nondiabetic groups in corneal ECD (2480 ± 223 cells/mm2 for DM group vs. 2652 ± 234 cells/mm2 for non-DM), hexagonality (39.6 ± 2.8% for DM group vs. 47 ± 2.1% for non-DM), CV (42 ± 2.9% for DM group vs. 35.5 ± 2.3% for non-DM), and CCT (550 ± 14.8 µm for DM group vs. 530 ± 9.6 µm for non-DM). Patients who had diabetes for more than 10 years had significantly lower ECD (2356 cells/mm2 vs. 2689 cells/mm2), lower hexagonality (39 vs. 41%), and higher CV (43 vs. 41%) and higher CCT (553.9 ± 4.6 vs. 545.5 ± 4.0) than those with less than 10 years of diabetes. As the severity of DR increased, there was a significant decrease in ECD (from 2641 ± 194 cells/mm2 for mild NPDR to 2310 ± 82 cells/mm2 for severe PDR), a decrease in hexagonality (from 40.9 ± 3.2% for mild PDR to 37.4 ± 1.1% for severe PDR), an increase in CV (from 40.1 ± 2.3% for mild PDR to 44 ± 2.9% for severe PDR), and an increase in CCT (from 543.7 ± 13.8 for mild PDR 563.8 ± 2.9 for severe PDR). Conclusion This study revealed that type 2 diabetes is associated with significant reductions in ECD and hexagonality, as well as an increase in CV and CCT. The severity of DR and the duration of diabetes were correlated with changes in these parameters. These findings underscore the need for a comprehensive evaluation of corneal health in diabetic patients.